Prediction of frequent acute respiratory infections in the first year of life in children with cerebral ischemia, survivors of cytomegalovirus infection in the neonatal period - L. V. Kravchenko; M. A. Levkovich; S. B. Berezhanskaya; A. A. Afonin; I. I. Krukier; O. Z. Puzikova; I. V. Panova; D. I. Sozaeva; V. A. Popova; A. V. Moskovkina; N. A. Drukker (LLC "Diagnostics and Vaccines", 2023)
Objective: to develop prognostic criteria for frequent respiratory diseases in the first year of life in children with cerebral ischemia who had a cytomegalovirus infection in the neonatal period. Research methods: 73 children of the first year of life with cerebral ischemia, who underwent cytomegalovirus infection in the neonatal period, were deployed. All observed patients at the age of three months underwent a study of the population composition of peripheral blood T-lymphocytes using flow cytometry for the expression of membrane markers, taking into account the results on a Beckman Coulter Epics XL II laser flow cytometer. Typing of lymphocytes was carried out using monoclonal antibodies to differentiation clusters CD3+, CD3+CD69+, CD3+CD71+, CD3+CD95+ from Immunotech (France). The observation groups consisted of 30 children (41.1%) with frequent acute respiratory infections (4-5 episodes per year) in the first year of life and 43 people (58.9%) - children with no acute respiratory infection'sepisodes in the first-year life. Results. From the set of studied T-lymphocytes, statistically significant for the prognosis of frequent acute respiratory infections in the first year of life in children with cerebral ischemia who underwent cytomegalovirus infection in the neonatal period were found: CD3+ CD71+, CD3+ CD95+. It was revealed that in children with a reduced level of CD3+ CD71+ and an increased level of CD3+ CD95+ in blood serum at the age of 3 months, frequent acute respiratory infections occurred in the first year of life.